2009
DOI: 10.1371/journal.ppat.1000579
|View full text |Cite|
|
Sign up to set email alerts
|

The Chlamydia Type III Secretion System C-ring Engages a Chaperone-Effector Protein Complex

Abstract: In Gram-negative bacterial pathogens, specialized chaperones bind to secreted effector proteins and maintain them in a partially unfolded form competent for translocation by type III secretion systems/injectisomes. How diverse sets of effector-chaperone complexes are recognized by injectisomes is unclear. Here we describe a new mechanism of effector-chaperone recognition by the Chlamydia injectisome, a unique and ancestral line of these evolutionarily conserved secretion systems. By yeast two-hybrid analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 65 publications
(121 reference statements)
8
143
1
Order By: Relevance
“…Previous studies have revealed that CopB is secreted via a T3S mechanism and is detectible by immunolocalization in a pattern consistent with inclusion membrane localization (15). Similarly to Yersinia YopB, CopB interacts with a T3S chaperone (Scc2) that is encoded immediately upstream from its own gene (15,49). Scc2 also interacts with CopD, the putative YopD-like translocator component (49).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous studies have revealed that CopB is secreted via a T3S mechanism and is detectible by immunolocalization in a pattern consistent with inclusion membrane localization (15). Similarly to Yersinia YopB, CopB interacts with a T3S chaperone (Scc2) that is encoded immediately upstream from its own gene (15,49). Scc2 also interacts with CopD, the putative YopD-like translocator component (49).…”
Section: Discussionmentioning
confidence: 74%
“…Similarly to Yersinia YopB, CopB interacts with a T3S chaperone (Scc2) that is encoded immediately upstream from its own gene (15,49). Scc2 also interacts with CopD, the putative YopD-like translocator component (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these data indicate that there is a C-ring in the injectisome even though it could not be visualized by cryo-EM thus far. It would form a platform at the cytoplasm/inner membrane interface for the recruitment of the ATPase complex (see below) (Jackson and Plano, 2000) and substratechaperone complexes (Morita-Ishihara et al, 2006;Spaeth et al, 2009). …”
Section: The C-ringmentioning
confidence: 99%
“…CdsD has been shown to interact with the cytoplasmic ATPase CdsN and with CdsL, a possible negative regulator of ATPase activity [35]. A complex network of interactions has been shown to occur in vitro between CdsQ, CdsD, CdsN, and CdsL [35,49]. Upon assembly of the inner membrane and C-ring components, the machinery becomes secretion competent and secretes its needle subunits CdsF [27], possibly with the help of the putative molecular ruler protein CdsP [50].…”
Section: Type III Secretionmentioning
confidence: 99%